Contentment in the Light of the Prophet's Sunnah: An Objective Study - Isleem, Laila Mohammad Rajab (مركز البحث العلمي الاسلامي, 2021)
نظرا لأهمية القناعة في حياة الإنسان، ودورها في الاستقرار النفسي، وعدم التطلع لما في يد الآخرين تناولت دراسة هذا البحث والذي بعنوان "القناعة في ضوء السنة النبوية" دراسة موضوعية، حيث اشتمل البحث على تعريف القناعة لغة واصطلاحا، فضل القناعة وأجرها، الرضا بالمقسوم وهو على نوعين: الرضا بالقدر والرضا بالرزق، اليأس مما في أيدي الناس، ونماذج من حياة النبوة والصحابة رضي الله عنهم في القناعة. وكان من أهم النتائج التي توصلت إليها: أن الإنسان لو عاش في قناعة ورضا لانتهت كثير من المشكلات في حياته، ولما كان الحسد ولا الكمد، ولكن نقص الإيمان بهذا الخلق ولد الكثير من الأضغان والشحناء.
The study tackles the significance of contentment in people lives, its role in self stability, and giving up the hope of what others have. It is an objective study which includes the definition of contentment, the virtue of contentment and its reward, satisfaction with the allotted, which is of two types: Satisfaction with destiny and contentment with sustenance, despair of what other people have, and finally samples of contentment from the lives of the Companions. The results show that if a person is content, many problems will be solved in his/her life. It is neither envy nor hardship, but a lack of faith that caused a lot of hatred and malevolence among people.
Keywords: الاستقرار النفسي -- السنة النبوية -- حياة النبوة -- حياة الصحابة